HAMBATAN IMPLEMENTASI SISTEM MERIT PADA DINAS PUPR KABUPATEN BOGOR DALAM PENGELOLAAN INFRASTRUKTUR JALAN KABUPATEN; OBSTACLES OF MERIT SYSTEM IMPLEMENTATION IN PUBLIC WORKS AND PUBLIC HOUSING AGENCY OF BOGOR DISTRICT IN MANAGEMENT OF DISTRICT ROAD INFRAST - rusli andy (Badan Kepegawaian Negara | The National Civil Service Agency, 2019)
This study describes the barriers to the merit system implementation in Public Works and Public Housing Agency in Bogor regency and its implications for the management of district road infrastructure. The empirical problem that arises is that the management of road infrastructure that is not optimal is indicated by the increase of damaged roads and stagnation in the length of Regency roads, which has implications for the emergence of community complaints. This condition is allegedly due to the weak capability of employees in the Public Works and Public Housing Agency which has not implemented the merit system. The research approach used is a qualitative method with primary data sources and secondary data. The results of the study show that there are staffing problems caused by the implementation of the merit system in the Public Works and Public Housing Agency, including aspects that have not been fulfilled in terms of quantity, quality, managerial and technical competence and the development of competencies. There are a number of obstacles in the implementation of the merit system, including the appointment of honorary staff, commitment of regional heads, the influence of the organizational environment, unmeasured performance assessment, limited competency development, unfinished job competency standards, incomplete competency mapping, career patterns that have not been implemented yet, and weak supervision from the Government. This condition has implications for the performance of the Public Works and Public Housing Agency in managing road infrastructure that is not optimal.(...)